Did the German court do Europe a favour? - Ashoka Mody (Bruegel, 2014)
The European Central Bank's Outright Monetary Transactions (OMT) programme was a politically-pragmatic tool to diffuse the euro-area crisis. But it did not deal with the fundamental incompleteness of the European monetary union. As such, it blurred the boundary between monetary and fiscal policy. The fuzziness of this boundary helped in the short-term but pushed political and economic risks to the future. Unless a credible commitment to enforcing losses on private creditors is instituted, these conundrums will persist. The German Federal Constitutional Court has helped by insisting that such a dialogue be conducted in order to achieve a more durable political and economic solution. A study of the European Union Court of Justice's Pringle decision (Thomas Pringle v Government of Ireland, Ireland and The Attorney General, Case C-370/12, ECJ, 27 November 2012) suggests that the ECJ will also not rubber-stamp the OMT - and, if it does, the legal victory will not resolve the fundamental dilemmas.
Keywords: 330